Vegetable oil-based lubricants - A review of oxidation - Fox, N; Stachowiak, Gwidon (Pergamon, 2007)
Vegetable oils are being investigated as a potential source of environmentally favourable lubricants, due to a combination of biodegradability, renewability and excellent lubrication performance. Low oxidation and thermal stability, poor low-temperature properties and narrow range of available viscosities, however, limit their potential application as industrial lubricants. This review addresses oxidation as a limitation of vegetable oil-based lubricants. The basic mechanism of vegetable oil autoxidation is presented, along with methods used to monitor and analyse the products of oxidation. The potential impact of such oxidation products on lubrication performance is discussed. A brief discussion of methods used to assess and improve oxidation stability completes the review.